How Did that Happen? Teachers' Explanations for Low Test Scores. Issue 2 (February 2019) - Evans, Margaret; Teasdale, Rebecca M.; Gannon-Slater, Nora; Londe, Priya G. La; Crenshaw, Hope L.; Greene, Jennifer C.; Schwandt, Thomas A.
Context: Educators often engage with student performance data to make important instructional decisions, yet limited research has analyzed how educators make sense of student performance data. In addition, scholars suggest that teachers recognize a relationship between their instruction and student performance data, but this is a relatively untested assumption. Focus of Study: We investigated if and how teachers referenced instruction as a contributing factor for why students performed in particular ways on assessments. We also studied other explanations that teachers offered for student performance data. Research Design: Our research team conducted a qualitative case study of six grade-level teams of teachers who met biweekly to make meaning of student performance data. Using data collected from 44 hours of observation of teacher team meetings, 16 individual interviews, and six group interviews with participating teachers, we analyzed the ways in which and the extent to which teachers referenced instruction as a contributing factor to student performance data. Findings: Teachers connected student performance data to their instruction approximately 15% of the time. Teachers more frequently connected student performance data to student characteristics. Notably, student behavior accounted for 32% of all teacher explanations for student performance. We offer five distinct categories of teachers' explanations of student performance and the extent to which teachers invoked each category. Conclusions: The findings in this study build on research on teachers' attributions for assessment data. In contrast to other studies, our findings suggest that teachers invoked student characteristics in distinct ways when explaining student performance. At times, teachers were knowledgeable about student characteristics, which offered verifiable insights into the "problem" of low achievement. At other times, teachers voiced negative viewpoints of students that served to blame students for their poor performance. We suggest that the practice of data-driven decision making offers an opportunity to bolster educators' informed judgment and undermine negative, unverifiable claims about children.